Pengaruh Media Sosial Terhadap Perilaku Konsumen : Studi Kasus Instagram dan Pembelian Produk Fashion - Nursapia Harahap; Hafiz Mansyur; Nadya Dwi Ananda; Dwi Arlintang; Elisa Damayanti; Susan Ramadhani; Nisrina Ardra Hafizha; Afrini Yuninda Silitonga; Rangga Diva (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to examine the influence of social media usage, particularly Instagram, on consumer behavior in the context of fashion product purchases. The method used in this research is a quantitative approach, with data collected through questionnaires distributed to respondents. The results show that Instagram usage has a significant impact on the frequency of fashion product purchases. The t-test reveals that each additional hour of Instagram use per day significantly increases the frequency of fashion purchases. These findings indicate the importance of Instagram as an effective marketing platform in the fashion industry.